Morphological study of pancreatic duct in red jungle fowl - Khadim, Khalid Kamil; Abu Bakar @ Zakaria, Md Zuki; Babjee, Shaik Mohamed Amin; Saad, Mohd Zamri (Academic Journals, 2010)
Morphological and histochemical study of the pancreas and pancreatic ducts of ten adult red jungle fowl (Gallus gallus spadiceus) were carried out by means of light microscopy. The bulk of the pancreas consists of a dorsal, ventral, third and small splenic lobe. Three pancreatic ducts were recognized as they join the proximal end of the ascending duodenum. The exocrine units were composed of main pancreatic tissues, while the endocrine units were observed frequently in the third and splenic lobes. A single layer of pyramidal cells with acidophilic zymogen granules and small centro-acinar cells were formed in the exocrine acinus. The intercalated duct was lined by flattened epithelium which changed to cuboidal in the intralobular duct, while the interlobular and main pancreatic ducts were lined by simple columnar epithelium. Three types of cells were detected within the surface epithelium: principal, light and basal cells. These cells possess short luminal projections with a fuzzy surface coat. Apical neutral and sulfomucin reaction indicated involvement of these epithelial with secretion. Neither goblet cells nor ductal glands were found in the pancreatic ducts. Secretion of both neutral and sulfated materials by the epithelial lining the pancreatic ducts, suggesting that they are acting not only to facilitate the transport of the pancreatic juice, but also as a protective barrier to protect the gland from autodigestion.